A modern history of Tanganyika - Iliffe, John. (Cambridge Cambridge University Press, 1979)
This is the first comprehensive and fully documented history of modern Tanganyika (mainland Tanzania). After introductory chapters on the nineteenth century, Dr Iliffe concentrates on the colonial period, and especially on economic, social and intellectual change among Africans as the core of their colonial experience and the basis of their political behaviour. Particularl attention is paid to the consequences for small-scale societies of their incorporation into the international order; the impact of capitlaism and the emergence of capitalist relationships and attitudes; African attempts to defend or reform indigenous institutions and to organise movements of protest or revolt against European control; the successive formation and dissolution of a specifically colonial society; and the effects of economic change on Tanganyika's ecology in modern times. The book brings together the research which scholars of many nationalities have carried out in Tanzania over the last twenty years, and attempts to synthesise their findings with the evidence available from African and European records in Tanzania, Britain and Germany.
Includes index.
Keywords: Tanzania--History--1964-